Dynamic Changes in Viral Loads during Co-Infection with a Recombinant Turkey Herpesvirus Vector Vaccine and Very Virulent Marek’s Disease Virus In Vivo - Tian Ding; Min Xiong; Yang Xu; Xing Pu; Qin-sen Wang; Mo-ru Xu; Hong-xia Shao; Kun Qian; Hai-bin Dang; Ai-jian Qin (Viruses, 2024)
Marek’s disease (MD), caused by the Marek’s disease virus (MDV), is a common infectious tumor disease in chickens and was the first neoplastic disease preventable by vaccination. However, the vaccine cannot completely prevent virulent MDV infections, allowing both the vaccine and virulent MDV to coexist in the same chicken for extended periods. This study aims to investigate the changes in viral load of the very virulent strain Md5 and the rHVT-IBD vaccine in different chicken tissues using a real-time PCR assay. The results showed that the rHVT-IBD vaccine significantly reduced the viral load of MDV-Md5 in different organs, while the load of rHVT-IBD was significantly increased when co-infected with Md5. Additionally, co-infection with Md5 and rHVT-IBD in chickens not only changed the original viral load of both viruses but also affected the positive rate of Md5 at 14 days post-vaccination. The positive rate decreased from 100% to 14.29% (feather tips), 0% (skin), 33.33% (liver), 16.67% (spleen), 28.57% (thymus), 33.33% (bursa), and 66.67% (PBL), respectively. This study enhances our understanding of the interactions between HVT vector vaccines and very virulent MDV in chickens and provides valuable insights for the future development of MD vaccines.